Original article Research on alteration of neurons in vagal nuclei in medulla oblongata in newborns with respiratory distress - Islami, Hilmi; Shabani, Ragip; Shabani, Driton; Dacaj, Ramadan; Manxhuka, Suzana; Azemi, Mehmedali; Krasniqi, Shaip; Kurtishi, Ilir (Folia Neuropathologica, 2011)
Neuronal and axonal degenerative changes in motor vagal neurons (DMNV) and sensory vagal neurons (nTS) in the medulla oblongata in newborns were studied. Material was taken from the autopsies of newborns, live and dead newborns, in different gestational weeks (aborted, immature, premature and mature). 46 cases were studied. Material for research was taken from the medulla oblongata and lung tissue. Serial horizontal incisions were made in the medulla oblongata (± 4 mm), commencing from the obex, where the DMNV and nTS vagal nuclei were explored. Fixed cuttings in buffered formalin (10%) were used for histochemical staining. Serial cuttings were done with a microtome (7 µm). Pulmonary infections, being significant (p < 0.05), have an important place when studying respiratory distress (RD) in newborns. Morphological changes of nerve cells in DMNV and nTS nuclei in the medulla oblongata in newborns in different gestational weeks are more emphasized in matures in comparison to aborted and immature (p < 0.05). Depending on the lifetime of dead newborns, neuronal morphological changes in vagus nerve nuclei are significant (p < 0.05). Therefore, it can be concluded that pulmonary infections are often caused due to dramatic respiratory distress in newborns, while hypoxaemic changes in the population of vagus nerve neurons in respiratory distress are more emphasized in matures.